Optimization of Dengue-EDIII – Hepatitis B-VLP Fusion Antigen Protein Expression in Mammalian Cell Systems and Preliminary Immunogenicity Testing in Mice - Ziza Putri Aisyia Fauzi; Eka Nur Fatmawati; Putri Tri Hartini; Yuneka Saristiana; Husnunnisa (CV. Get Press Indonesia, 2025)
The development of a safe and effective dengue vaccine remains challenging due to the risk of antibody-dependent enhancement (ADE) associated with imbalanced immune responses. This study aimed to optimize the expression of a dengue virus envelope domain III (EDIII) fusion antigen displayed on Hepatitis B core antigen virus-like particles (VLPs) and to evaluate its preliminary immunogenicity in a murine model. Optimization of antigen design and expression conditions resulted in a substantial increase in VLP production compared with the non-optimized construct. The purified VLPs showed uniform size, proper particle assembly, and preserved antigenic integrity. Immunization of mice induced high titers of EDIII-specific IgG and strong serotype-specific neutralizing antibodies against dengue virus serotype 2, while no antibody-dependent enhancement was detected in vitro. These findings indicate that the optimized EDIII–HBcAg VLP platform is highly immunogenic and demonstrates a favorable safety profile, supporting its potential as a promising subunit vaccine candidate for dengue virus.